ICTV Virus Taxonomy Profile: Spinareoviridae 2022 - Matthijnssens, Jelle (2022)
Spinareoviridae is a large family of icosahedral viruses that are usually regarded as non-enveloped with segmented (9–12 linear segments) dsRNA genomes of 23–29 kbp. Spinareovirids have a broad host range, infecting animals, fungi and plants. Some have important pathogenic potential for humans (e.g. Colorado tick fever virus), livestock (e.g. avian orthoreoviruses), fish (e.g. aquareoviruses) and plants (e.g. rice ragged stunt virus and rice black streaked dwarf virus). This is a summary of the ICTV Report on the family Spinareoviridae, which is available at ictv.global/report/spinareoviridae.